Diseño de un plan de mantenimiento productivo en el área de servicios industriales en la empresa Láctea Tanilact - Macas Poma, Deicy Beatriz (2022)
This research project is developed in the Tanilact dairy company, located in the parish Tanicuchí, Latacunga canton, province of Cotopaxi, with the objective of designing the productive maintenance plan in the area of industrial services, mainly because the machinery they have has problems causing rework and this in turn economic losses due to costs of new supplies, wear of machinery and production stoppage. In order to fulfill the objective, descriptive research is used to know the characteristics and operation of the machines, facilitating the evaluation of the technical studies, and the field technique is also applied to be in direct contact with the machines of the industry. The results identify 43 machines and equipment distributed in 5 systems, which are: natural water, compressed air, steam, chilled water and electric energy. From the analysis of the results, it was determined that the steam system, consisting of three boilers of 100, 80 and 200 bhp, needs a change of the purge valves, and the other systems need periodic maintenance. According to the needs identified in the machines, the activities and frequencies to be carried out in the maintenance plan are detailed. The design of the productive maintenance plan is carried out through a Microsoft Excel software in which automatic maintenance actions are programmed and a record of the machines and equipment is kept.